Effect of Gas on Burst Proneness and Energy Dissipation of Loaded Coal: An Experimental Study Using a Novel Gas-Solid Coupling Loading Apparatus. (7th January 2021) - Wang, Zuguang; Li, Huamin; Wang, Shen; Gao, Baobin; Wang, Wen
Abstract : Deep coal mining is seriously affected by a combined dynamic disaster of rock burst and coal and gas outburst, but the influence mechanism of gas on this combined dynamic disaster is still not very clear, which is significantly different from the single type disasters. In this study, to explore the effect of gas on the coal-rock burst, a novel gas-solid coupling loading apparatus is designed to realize gas adsorption of coal sample with burst proneness and provide uniaxial loading environment under different gas pressure. A series of uniaxial compression tests of gas-containing coal with different gas pressure is carried out, and the energy dissipation process is monitored by an acoustic emission (AE) system. Results show that the macroscopic volume strain of the coal sample increases as gas adsorption and gas pressure increase under constant uniaxial loading pressure. Gas has the ability to expand the pores and natural fractures in coal sample by mechanical and physicochemical effects, which leads to a degradation in microstructure integrity of coal sample. With the increase of gas pressure, both the macrouniaxial compression strength (UCS) and elastic modulus show a downward trend; the UCS and elastic modulus of coal samples with 2 MPa gas pressure reduce by 58.78% and 48.82%, respectively, compared to those of the original coal samples. The main reason is that gas changes the pore-fissure structure and the mesoscopic stress environment inside the coal sample. Owing to the gas, the accumulated elastic energy of the gas-containing coal samples before failure reduces significantly, whereas the energy dissipated during loading increases, and the energy release process in the postpeak stage is smoother, indicating the participation of gas weakens the burst proneness of the coal sample. This study is of important scientific value for revealing the mechanism of combined dynamic disaster and the critical occurrence conditions of coal-rock burst and coal and gas outburst.